Elaboración del estudio de pre-factibilidad para el montaje de una empresa de servicios de selección, limpieza y reacondicionamiento de materiales de empaque y productos cosméticos en Bogotá. (2017)
This work contains a prefeasability study about the creation of a company that provides services in selection, cleaning and packaging of finish products and packaging materials for cosmetic industry, in order to have a positive return of an inversion.